Implementación De Un Robot Movil Prototipo Para Descarga De Semilla En Hileras De Terreno Preparado Para Cultivo (2023)
This document presents a degree work, in the electronic engineering program of the Villavicencio branch of the Antonio Nariño University, in which an autonomous prototype mobile robot is developed that can unload seeds in rows of land prepared for cultivation. The robot has a caterpillar type locomotion system which makes it more stable and with better maneuverability on uneven terrain, in addition to having a LIDAR sensor, which is used to collect information from the environment and implement a reactive autonomous navigation system, allowing a better precision of the robot's movement taking as a reference point an obstacle on one side of the robot, it also has an IMU (Inertial Measurement Unit), which is used to maintain a fixed direction throughout the process of unloading seeds. The IMU is able to detect any changes in the robot's orientation, and sends signals to the control system to correct any deviations, thus allowing the robot's electromechanical system, which is responsible for storing and releasing the seeds into the field at regular intervals, to do so more efficiently. To carry out all the autonomous operation of the robot, a Raspberry Pi 4 is used as a central controller, being this our main component for the development of the project presented in this report. Keywords: (IMU, Mobile Robot, Electromechanical System, Controller)